Method for delithiating at least one lithium transition metal nitride
By mixing the oxidant with lithium transition metal nitride for delitting, the problem of lithium deposition of negative electrode materials in lithium-ion batteries under high charging current is solved, and a negative electrode material with high working potential and good performance is obtained, suitable for lithium Ion battery.
Patent Information
- Application Number
- CN202280089768.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-23
- Publication Date
- 2025-01-10
AI Technical Summary
The negative electrode materials in existing lithium-ion batteries are prone to lithium deposition under high charging current and weak working potential, resulting in reduced battery capacity and safety problems. The working potential of existing lithium transition metal nitride materials is limited, and their performance is not satisfy.
By mixing the oxidant with the lithium transition metal nitride and performing deliquefaction, the obtained material can avoid the initial discharge step, and is used for the negative electrode active material of the lithium-ion battery, including mixing, recycling, centrifugation, rinsing and vacuum drying. Adjust the molar ratio and temperature.
It achieves avoiding lithium deposition, improving battery capacity and safety, and provides a negative electrode material with high working potential and good performance, suitable for lithium-ion batteries.
Smart Images

Figure HDA0004957646450000011 
Figure HDA0004957646450000012 
Figure HDA0004957646450000021
Abstract
Description
Technical Field
[0001] The present invention relates to a delithiation method for delithiation of special materials (lithium transition metal nitrides). The present invention also relates to the use of a material obtained by the method as a negative electrode material for lithium ion batteries. Background Art
[0002] Typically, a lithium-ion battery includes one or more positive electrodes, one or more negative electrodes, an electrolyte, and a separator.
[0003] Lithium-ion batteries are increasingly being used as autonomous energy sources, in particular in applications related to electric vehicles. This trend is due in particular to the significantly greater mass and volume energy density than conventional nickel-cadmium (Ni-Cd) and nickel-metal hydride (Ni-MH) batteries, the absence of a memory effect, the low self-discharge compared to other batteries, and the reduced cost per kilowatt-hour associated with this technology.
[0004] Lithium-ion batteries include electrode active materials that allow the insertion and exfoliation of lithium ions during the charging and discharging processes. These insertions and exfoliations need to be reversible to enable the battery to store energy over multiple cycles.
[0005] The good mobility of lithium ions in the structure and the good conductivity of the electrode materials are the fundamental features that enable the use of these batteries at high charging and discharging speeds, to authorize high electrical powers. The specific power of the battery is an important key for automotive applications because it enables the use of lighter batteries for the same force or it enables the use of the battery under safer conditions.
[0006] Rapid charging of lithium-ion batteries is also a key factor in the context of the development of hybrid and other electric vehicles.
[0007] Currently, the positive electrode materials used in lithium-ion batteries are lithiated transition metal oxides (e.g., LiCoO 2 、LiNi 0.6 Mn 0.2 Co 0.2 O 2 、LiFePO 4 Or LiMn 2 O 4 The negative electrode material itself is an insertion material (e.g., graphite or lithium titanate (Li 4 Ti 5 O 12 )).
[0008] During the charging process, the lithium ion Li +It is either extracted from the positive electrode material and intercalated into layers (in the case of graphite) or intercalated into crystal sites of the negative electrode material (in the case of lithium titanate).
[0009] When the charging current is high and when the operating potential of the negative electrode material is too weak, lithium is likely to be deposited on the negative electrode, which will result in a decrease in the capacity of the battery cell and may cause penetration into the separator and serious safety problems.
[0010] Lithium titanate is an advantageous material for high power batteries because its high operating potential (1.5 V vs Li+ / Li) is suitable for avoiding lithium plating. However, the capacity of lithium titanate remains limited compared to graphite. In fact, the capacity of graphite is more than twice that of lithium titanate.
[0011] Nitride-based electrode materials (particularly, lithium transition metal nitrides (e.g., Li 7 Mn 4 and Li 3 FeN 2 )). These materials have a capacity that is almost twice that of lithium titanate and have 7 Mn 4 The working potential of vs. Li+ / Li is 1.18V and the working potential of Li 3 FeN 2 The working potential is 1.25V vs.Li+ / Li and the performance is good under high current.
[0012] These materials (Li 7 Mn 4 and Li 3 FeN 2 ) have been described in patent document US5702843, these materials are used as electrode materials for secondary batteries. The advantage of using these materials as electrode materials is particularly related to the fact that the materials available for electrodes can be directly applied. However, as shown in patent document US5702843, the working potential of these materials is limited for use in battery cells. Therefore, the performance in battery cells is not satisfactory.
[0013] Therefore, there is still a need to develop electrode materials that can overcome the above-mentioned defects.
[0014] It is therefore an object of the present invention to provide a delithiation method for delithiating lithium transition metal nitrides, which delithiation method enables a material to be obtained which can be used as a negative electrode active material for lithium ion batteries. Summary of the invention
[0015] The object of the present invention is therefore to provide a delithiation method for delithiation of at least one lithium transition metal nitride, the delithiation method comprising the following steps:
[0016] a) mixing at least one oxidizing agent with the lithium transition metal nitride;
[0017] b) recovering the material obtained at the end of step a).
[0018] The method according to the invention makes it possible to obtain a delithiated material. This material makes it possible to avoid the initial discharge step usually performed in a battery cell having a material commonly used in the prior art (e.g., a chemical formula of Li 7 Mn 4 Or Li 3 FeN 2 In fact, these materials are not delithiated materials. Therefore, when these materials are used in a battery cell, an initial discharge step for discharging the battery cell is required.
[0019] The present invention also aims to provide the use of a material obtained by the process according to the invention as negative electrode active material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Other advantages and features of the present invention will become more apparent from the following detailed description of the present invention and the accompanying drawings, in which:
[0021] Figure 1 The material Li 7 Mn 4 and a diffraction pattern of a material obtained at the end of the method according to the invention;
[0022] Figure 2A Is the material Li 7 Mn 4 The photographs were observed using a scanning electron microscope.
[0023] Figure 2B is a photograph observed with a scanning electron microscope of the material obtained at the end of the process according to the invention;
[0024] Figure 3 is a diagram showing the galvanostatic curve of the material vs metallic Li obtained at the end of the method according to the invention. DETAILED DESCRIPTION
[0025] It is stipulated that the expression “from . . . to . . ” used in the description of the present invention is understood to include each of the mentioned endpoints.
[0026] The expression "at least one" is understood to mean one or more.
[0027] As described above, according to step a) of the method according to the invention, at least one oxidizing agent is mixed with the lithium transition metal nitride.
[0028] Advantageously, the one or more transition metals are selected from Mn, Fe, Co, Ni, Cu and mixtures thereof.
[0029] Preferably, the lithium transition metal nitride is selected from the group consisting of 7 Mn 4 , Li 3 FeN 2 , Li 2.6 Co 0.4 N.Li 2.0 Ni 0.67 N and Li 2.57 Cu 0.43 N material.
[0030] More preferably, the chemical formula of the lithium transition metal nitride is Li 7 Mn 4 or chemical formula is Li 3 FeN 2 .
[0031] Preferably, the oxidizing agent is selected from the group of oxidizing agents belonging to the metallocene family in oxidized form.
[0032] Advantageously, the oxidizing agent is chosen from cobalt salts, preferably from cobaltocene hexafluorophosphate, cobaltocene tetrafluoroborate, hexafluorophosphate bis(pentaméthylcyclopentadienyl)cobalt hexafluorophosphate, hexafluorophosphate tétrafluoroborate bis(pentamethylcyclopentadienyl)cobalt hexafluorophosphate and mixtures thereof.
[0033] More preferably, the oxidizing agent is selected from cobaltocene hexafluorophosphate.
[0034] According to a preferred embodiment, the molar ratio between the oxidant and the lithium transition metal nitride is from 0.5 to 3, preferably from 1 to 2.
[0035] Preferably, step a) is carried out in the presence of at least one solvent.
[0036] Advantageously, the solvent is selected from aprotic organic solvents, preferably selected from acetonitrile, tetrahydrofuran, dimethylformamide, dichloromethane, ethyl acetate and mixtures thereof, preferably selected from acetonitrile.
[0037] According to another embodiment, any solvent that can be used in the electrolyte of a lithium-ion battery can also be used. Preferably, the solvent is selected from ethylene carbonate (labeled "EC"), propylene carbonate (labeled "PC"), dimethyl carbonate (labeled "DMC"), diethyl carbonate (labeled "DEC") and ethyl methyl carbonate (labeled "EMC") and mixtures thereof.
[0038] According to another embodiment, a solvent selected from aprotic organic solvents (e.g., the aprotic organic solvents mentioned above) can be mixed with a solvent that can be used in the electrolyte of a lithium-ion battery (e.g., the solvents mentioned above).
[0039] Preferably, the solvent is acetonitrile.
[0040] As described above, according to step b) of the method according to the present invention, the material obtained at the end of step a) is recovered.
[0041] Advantageously, the material can be recovered by centrifugation or by filtration.
[0042] Next, the material is rinsed with a solvent (preferably a solvent selected from the solvents mentioned above), optionally rinsed multiple times.
[0043] Then, the material can be dried under vacuum.
[0044] Thus, the material Li 7-x MnN 4 (0 < x ≤ 2) and Li 3-y FeN 2 (0 < y ≤ 1.2) can be obtained.
[0045] The object of the present invention also lies in providing a use of a material obtained by the method according to the present invention, and the material is used as a negative electrode active material for a lithium-ion battery.
[0046] As described above, the method according to the present invention is a delithiation method for delithiating at least one lithium transition metal nitride.
[0047] According to the following examples, a delithiation protocol for delithiating at least one lithium transition metal nitride can be described.
[0048] Advantageously, first, an oxidizing agent (eg, the oxidizing agent mentioned above) may be added to a solvent (eg, the solvent mentioned above) to obtain a solution including the oxidizing agent.
[0049] Then, the lithium transition metal nitride (e.g., Li 7 Mn 4 or Li 3 FeN 2 ) may be added to the solution. The lithium transition metal nitride may be in the form of a powder.
[0050] The amount of the lithium transition metal nitride may be adjusted such that a molar ratio between the oxidant and the lithium transition metal nitride may be from 0.5 to 3, preferably from 1 to 2.
[0051] Next, the lithium transition metal nitride may be mixed into the solution including the oxidizing agent.
[0052] The temperature can thereby be adjusted to temperatures from -5°C to 50°C.
[0053] All of these steps can be performed in a regulated environment (eg, in a glove box).
[0054] Advantageously, the oxidizing agent used may be a cyclopentadienyl cobalt salt. The color of the solvent may change during the reaction. This thus constitutes a signal indicating that the reaction is ongoing.
[0055] At the end of the reaction, the material obtained can be recovered.
[0056] Advantageously, the material may be separated from the solution by centrifugation or by filtration.
[0057] The material can thus be washed several times with the solvent in order to remove any possible undesired products. The material can then be dried under vacuum.
[0058] The present invention will now be described in more detail by way of examples, which in no way limit the scope of the present invention. However, the examples enable specific features, variants and preferred embodiments of the present invention to be supported.
[0059] Example
[0060] Example 1: Method according to the present invention
[0061] The chemical formula is Li 7 Mn 4 A lithium transition metal nitride is used.
[0062] like Figure 1 As shown above (curve A, material A), the diffraction pattern of the material in the initial state is implemented.7 Mn 4 Characteristic peaks can be identified in the diffraction pattern.
[0063] like Figure 2A As shown above (Material A), a photograph of the material in its initial state observed using a scanning electron microscope was carried out.
[0064] The delithiation was performed in a glove box at a temperature of 20° C. The molar ratio between the oxidant and the lithium transition metal nitride was 1.5.
[0065] About 320 mg (0.002 mol) of Li 7 Mn 4 was placed in a conical flask, and then about 7.5 mL of acetonitrile and a magnetic bar were introduced into the same conical flask. About 1 g of cobalt hexafluorophosphate (0.003 mol) was dissolved in 7.5 ml of acetonitrile to prepare an oxidant solution. The oxidant solution was introduced dropwise by using an addition ampoule. A total of 15 ml of acetonitrile was used, and the concentration of the oxidant solution was 0.5 mol / L. After the addition, intense mixing was maintained during the night to carry out the reaction between the oxidant and the nitride.
[0066] Next, the mixture was decanted and transferred into a centrifuge tube. Centrifugation was performed by using a centrifuge at a speed of 5000 rpm during 5 minutes. After the centrifugation, the powder and the solution were separated.
[0067] About 5 mL of acetonitrile was introduced into the centrifuge tube a second time to perform washing, and then a second centrifugation was performed.
[0068] This washing-centrifugation step is repeated several times (3 times).Finally, the powder is placed in an oven (Buchi type oven) to dry at 90°C under vacuum during one hour.
[0069] The delithiated material is obtained after said drying.
[0070] Thus, the material is obtained at the end of the method according to the invention.
[0071] Thus, the diffraction pattern of the obtained material is implemented as Figure 1 As shown above (curve B, material B).
[0072] Scanning electron microscopic photographs of the material obtained at the end of the process according to the invention were also carried out, such as Figure 2B As shown above (Material B).
[0073] Obviously, the chemical formula is Li 7 Mn4 The material has changed.
[0074] More precisely, in fact, the chemical formula is Li 5.3 Mn 4 The material was obtained. Due to the lattice parameters calculated based on the diffraction pattern (which is ), chemical formula is Li 5.3 Mn 4 The presence of the material is confirmed.
[0075] Therefore, for the chemical formula Li 7 Mn 4 The delithiation of the material is carried out by the method according to the invention.
[0076] Example 2: Use of the material obtained in Example 1 in a semi-cell
[0077] The active material obtained in Example 1 was prepared in the form of a composite electrode and tested with a metallic lithium part in a button cell CR2032. The composite electrode was prepared by mixing 70% by weight of the active material obtained in Example 1 with 22% by weight of acetylene black and 8% by weight of tetrafluoroethylene (PTFE).
[0078] The separators used are separators made of glass microfibers sold by Whatman CAT
[0080] The electrolyte used was 1 mol / L lithium hexafluorophosphate dissolved in a carbonate solvent mixture having a volume ratio of 1:1:1 of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC).
[0081] Then, the half-cells are assembled. The assembly of the half-cells is carried out in a glove box.
[0082] Electrochemical testing
[0083] like Figure 3 As shown above, constant current cycling was performed with a VMP3 potentiostat from BioLogic at a cycle rate of C / 20. The potential window was between 1.6V and 0.9V.
[0084] exist Figure 3 In , the starting point x=0 corresponds to the active material obtained at the end of Example 1. The potential at this point is E=1.7V.
[0085] When x increases, the material is electrochemically reduced, and the potential of the material decreases. It is known that when the potential drops to E = 0.9 V, the initial form Li 7 Mn4 Thus, Figure 3 It is observed that when E = 0.9 V, x is approximately equal to 1.7. In other words, when E = 0.9 V, approximately 1.7 lithium is electrochemically reinserted into the half-cell. Therefore, when x = 0, the chemical formula can be determined to be Li 5.3 Mn 4 .
[0086] Thus, the material obtained by the process according to the invention is of the formula Li 7-x Mn 4 (wherein x=1.7), the material is thus delithiated.
[0087] The material can be used as a negative electrode active material for lithium ion batteries.
Claims
1. A method for delithiation of at least one lithium transition metal nitride, the delithiation method comprising the following steps: a) mixing at least one oxidizing agent with the lithium transition metal nitride; b) recovering the material obtained at the end of step a).
2. The delithiation method according to claim 1, characterized in that: The one or more transition metals are selected from Mn, Fe, Co, Ni, Cu and mixtures thereof.
3. The delithiation method according to claim 1 or 2, characterized in that: The lithium transition metal nitride is selected from the chemical formula of Li7MnN4, Li3FeN2, Li 2.6 Co 0.4 N.Li 2.0 Ni 0.67 N and Li 2.57 Cu 0.43 N material.
4. The delithiation method according to any one of the preceding claims, characterized in that: The chemical formula of the lithium transition metal nitride is Li7MnN4 or Li3FeN2.
5. The delithiation method according to any one of the preceding claims, characterized in that: The oxidizing agent is selected from cobaltocene salts, preferably selected from cobaltocene hexafluorophosphate, cobaltocene tetrafluoroborate, bis(pentamethylcyclopentadienyl)cobalt hexafluorophosphate, bis(pentamethylcyclopentadienyl)cobalt hexafluorophosphate tetrafluoroborate and mixtures thereof.
6. The delithiation method according to any one of the preceding claims, characterized in that: The molar ratio between the oxidant and the lithium transition metal nitride is from 0.5 to 3, preferably from 1 to 2.
7. The delithiation method according to any one of the preceding claims, characterized in that: Step a) is carried out in the presence of at least one solvent.
8. The delithiation method according to claim 7, characterized in that: The solvent is selected from aprotic organic solvents, preferably selected from acetonitrile, tetrahydrofuran, dimethylformamide, dichloromethane, ethyl acetate and mixtures thereof, preferably selected from acetonitrile.
9. The delithiation method according to claim 7, characterized in that: The solvent is selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and a mixture thereof.
10. Use of a material obtained by a delithiation process as defined in any one of the preceding claims as a negative electrode active material for a lithium ion battery.
Citation Information
Patent Citations
Nonaqueous secondary battery
US5702843A